Assessment of the association between dysphagia and sarcopenia among elderly patients with cirrhosis: Usefulness of the finger-ring test. (July 2021) - Haraguchi, Masafumi; Miyaaki, Hisamitsu; Nakamura, Yutaka; Narita, Syouhei; Matsumoto, Kousuke; Fukushima, Masanori; Sasaki, Ryu; Miuma, Satoshi; Takahata, Hideaki; Yamaguchi, Naoyuki; Nakao, Kazuhiko
Highlights: Liver cirrhosis is a late stage of irreversible fibrosis of the liver. Patients with decompensated cirrhosis often have muscle atrophy and sarcopenia. sarcopenia negatively affects the prognosis of patients with cirrhosis. the proportion of patients with dysphagia has increased due to aging. EAT-10 and finger-ring test can be used to screen for sarcopenia-related dysphagia. Abstract: Aim: Sarcopenic dysphagia has become an urgent matter of debate in our aging society. However, little is known about the relationship between sarcopenia and dysphagia in patients with liver cirrhosis. Our aim was to assess sarcopenia and dysphagia among elderly patients with cirrhosis using two easy-to-use screening tests, i.e., the eating assessment tool-10 and the finger-ring test. Methods: The eating assessment tool-10, handgrip strength, skeletal muscle mass index, computed tomography, and the finger-ring test were included in our analysis. One hundred patients with cirrhosis and without a history of aspiration pneumonia were divided into the elderly (≥75 years) and non-elderly (<75 years) groups. Results: In the elderly group, sarcopenia was identified in 56.5% of the patients; of these, 30.4% and 13.0% had eating assessment tool-10 scores of ≥2 and ≥3, respectively. Sarcopenia-related factors correlated significantly with the eating assessment tool-10 scores ( p <0.01). Multivariate regression analysis revealed that sarcopenia was significantly associated with dysphagia ( p =0.028; odds ratio, 7.27). Among the elderly patients, the calf size of the non-dominant lower limb was less than the finger-ring circumference in 37.0% of the patients. This group had a significantly higher proportion of patients with an eating assessment tool-10 score of ≥2 than those with a greater calf than finger-ring circumference ( p <0.01). Conclusions: Sarcopenia, rather than the hepatic reserve function, is associated with dysphagia among elderly patients with cirrhosis. The finger-ring test might be useful in screening for dysphagia.